2014
DOI: 10.7906/indecs.12.4.2
|View full text |Cite
|
Sign up to set email alerts
|

Design Pattern Canvas: An Introduction to Unified Serious Game Design Patterns

Abstract: The aim of this article is to start a dialogue and search for a unified game design tool within the game design and research community. As a possible direction, presented paper outlines the practice and importance of design pattern use in serious game development and argues that design patterns can make serious game development more efficient by enabling knowledge exchange and better communication between different stakeholders. Furthermore, the use of design patterns provides a foundation for structured resea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Some research work in the field of serious gaming frameworks exists. In particular, for the use of design patterns [12][13][14], approaches have been based on problem-based learning [15][16][17][18], deep learning [19,20], RETAIN model of FutureLab [21,22], and Evidence-Centered Design [23][24][25]. In this study, we use the Design, Play, and Experience (DPE) framework [26] to study the characteristics of SGs.…”
Section: Study Of Characteristics Of Serious Gamesmentioning
confidence: 99%
“…Some research work in the field of serious gaming frameworks exists. In particular, for the use of design patterns [12][13][14], approaches have been based on problem-based learning [15][16][17][18], deep learning [19,20], RETAIN model of FutureLab [21,22], and Evidence-Centered Design [23][24][25]. In this study, we use the Design, Play, and Experience (DPE) framework [26] to study the characteristics of SGs.…”
Section: Study Of Characteristics Of Serious Gamesmentioning
confidence: 99%
“…A later definition is that Serious games are amusements that don't have diversion as their main role [17]. Serious games traverse over an extensive variety of fields, for example, instruction, treatment, promoting, protection, exploration, and so on and in light of the fact that there is no accord on the space limits for Serious games, a meaning of Serious games is still an open subject [18]. Some "particular" definitions mirror these distinctions and are utilized to compel a restricted perspective of the way of "Serious games" [19].…”
Section: Ementioning
confidence: 99%
“…The participating children suggested that the application could have been more interactive if it had been designed as a game [ 10 ]. When designing serious games such as these, there are several aspects that need to be considered, such as the purpose of the game, the end users, the stakeholders in the project, and how the game can engage the players [ 11 - 13 ]. Serious games are a way to learn and are meant to solve real world problems; in the best case, they are enjoyable and entertaining [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%